Combined effect of probiotics and omega-3 fatty acids on blood and liver function biomarkers and gut microbiota diversity in male mice with high fat diet-induced obesity - Kwang Hee Son; Jeongwook Lee; Hee-Young Yang; Yerim Heo; Jong Seo Lee; Dong-Seok Lee; Kum-Joo Shin; Tae-Jun Kwon (PLoS ONE, 2025)
This study investigates the combined effects of probiotics and omega-3 fatty acids on blood and liver function biomarkers, as well as gut microbiota diversity, in a high-fat diet (HFD)-induced obesity model in male mice. Cardiovascular diseases (CVD), often linked to obesity, are major global health issues driven by abnormal cholesterol and triglyceride levels in the blood. Omega-3 fatty acids, known to lower triglycerides and prevent CVD, and probiotics, which enhance gut microbiota balance and nutrient absorption, were evaluated for their combined effects. The experiment involved five groups of male C57BL/6J mice: a normal diet group, an HFD group, an HFD + probiotics group, an HFD + omega-3 group, and an HFD + combined probiotics and omega-3 group. Over six weeks, the combined treatment group showed significant reductions in body weight gain, a significant improvement in ALT levels (a key liver function biomarker), and enhanced anticoagulation markers, such as prothrombin time and activated partial thromboplastin time, compared to the HFD group. Gut microbiota analysis via 16S rRNA sequencing also revealed significant increases in microbial diversity in the combined treatment group. These findings suggest that co-administration of probiotics and omega-3 offers potential therapeutic benefits in reducing obesity-related metabolic dysfunctions by improving lipid metabolism, liver health, and blood circulation.